ESTUDO DOS INTERFERENTES NA DETERMINAÇÃO DO NÚMERO DE ACIDEZ TOTAL (NAT) EM PETRÓLEO - Fernandes, Hayane Amorim (2020)
The standard method for determination of the total acid number (TAN) crude oil is the ASTM D664, which uses potentiometric titration in non-aqueous solvents. In this paper, the interference of the salts NaCl, CaCl2, MgCl2, and SrCl2, in the TAN determinat